Halalan Toyyiban Poultry Feed: an Appraisal from the Maqasid Shariah Perspective - Mohd Ashraf, Amalina; Abd Rahman, Fadilah (International Journal of Engineering and Technology, 2018)
Animal feed is one of the essential elements in the production of Halal food products. In choosing animal-based Halal food products, a Muslim should be concerned not only about the sources of the animals and the slaughtering process, but also the way the animals were raised and fed. This is due to the emerging issues related to animal feeding, in which animals were being fed with unsuitable, unnatural feed, mainly because of the so-called ‘economic considerations’. Nevertheless, even though animal feed is an important element in Halal animal production, the position of Halalan toyyiban (permissible and safe) feed has often been neglected and less attention has been given to this matter. Halalan toyyiban poultry feed promises Halal and safe poultry meat and eggs for human consumption according to the injunctions of Shariah. Review of the literatures show that Halalan toyyiban issues include among others the issue of feed containing of non-Halal ingredients or filth, the development of pathogenic enteric microbes through antimicrobial resistance (AMR) bacteria in feed, genetically modified feed (GMF), the accumulation of mycotoxin, dioxin, heavy metals, pesticides and both medicated and non-medicated feed additives in poultry meat and eggs as well as physical hazards in farming areas. This paper attempts to examine the position of poultry feed from the Shariah point of view. More specifically, it appraises the position of current practice in poultry feed production from the Maqasid Shariah (Objectives of the Shariah) perspective. In so doing, it first reviews some of the literatures that highlight the emerging Halal and safety issues surrounding poultry feed. This is then followed by the description of the meaning and concept of Maqasid Shariah. Finally, the position of current practices in poultry feed production and feeding is appraised from the Maqasid Shariah viewpoint. It is further recommended that the safety, quality, cleanliness and the ingredients used in the production of animal feed must be regulated so as to ensure that poultry meat and its produce meet the safety requirements. To protect the interest of the Muslim consumers particularly in Malaysia, it is also recommended that a Halal standard for Animal Feed Production should be developed. By having this standard, growers of Halal livestock can have choices of feed and further, Muslim consumers can be rest assured that the poultry meats or its produce that they consumed are truly Halal.